Techniques and Outcomes of Medial Soft Tissue Release for Moderate to Severe Varus Deformity in Total Knee Arthroplasty: A Literature Review - Cheeva-akrapan, Vorasilp; Tanavalee, MD, Aree; Tanavalee, MD, Chotetawan; Ngarmukos, MD, Srihatach (Journal of Southeast Asian Orthopaedics, 2022)
Total knee arthroplasty for osteoarthritic knee with severe varus deformity always requires medial soft tissue release to reach a perfect outcome of the surgery. Up until now, there is still no consensus for the best technique of medial soft tissue release. This literature review collected and compared some aspects of each proposed techniques. The data were recruited from the PubMed and Google Scholar. The authors chose six medial soft tissue release techniques to be reviewed. These included subperiosteal release of superficial medial collateral ligament, pie-crusting technique, multiple needle puncture technique, medial epicondylar osteotomy, femoral origin release of the medial collateral ligament, and semimembranosus release. The results showed that each technique had a distinct superiority to each other. Each technique may be preferred in some situations. After a thorough discussion, the authors preferred the conventional subperiosteal release of superficial medial collateral ligament technique.